2020
DOI: 10.1111/jeb.13688
|View full text |Cite
|
Sign up to set email alerts
|

Intersexual differences in density‐dependent dispersal and their evolutionary drivers

Abstract: Many species nowadays live in increasingly fragmented landscapes, forming metapopulation systems with discrete habitat patches inhabited by spatially separated local populations (Hanski & Gaggiotti, 2004). In such a scenario, dispersal represents the crucial process that drives gene flow, thus constituting one of the major drivers of evolutionary processes in local populations such as allele frequency changes or founder effects (Clobert, Baguette, Benton, & Bullock, 2012). At the same time, dispersal abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Although most evidence for male sex-biased dispersal comes from mammals and birds (review: Li and Kokko 2019), laboratory studies such as Downey et al (2015) and Mishra et al (2020), which measured dispersal as crawling distance, show male-biased dispersal in insects like Callosobruchus and Drosophila respectively. A recent study also showed male biased dispersal in butterflies during the early breeding season, but female biased dispersal during the late season (Plazio et al 2020), suggesting that these differences were due to different reproductive strategies of males and females, which could also be the case in C. maculatus.…”
Section: Discussionmentioning
confidence: 93%
“…Although most evidence for male sex-biased dispersal comes from mammals and birds (review: Li and Kokko 2019), laboratory studies such as Downey et al (2015) and Mishra et al (2020), which measured dispersal as crawling distance, show male-biased dispersal in insects like Callosobruchus and Drosophila respectively. A recent study also showed male biased dispersal in butterflies during the early breeding season, but female biased dispersal during the late season (Plazio et al 2020), suggesting that these differences were due to different reproductive strategies of males and females, which could also be the case in C. maculatus.…”
Section: Discussionmentioning
confidence: 93%
“…From a behavioural perspective, females of P. teleius perform short-duration but frequent flights and devote more time to rest and oviposition, while males spend more time flying to explore their surroundings for receptive females [ 73 ]. Accordingly, male dispersal is typically promoted by the scarcity of females, while female dispersal is promoted by the lack of resources for oviposition [ 74 ]. This could easily explain the fact that, in our study, female dispersal increased more pronouncedly after mowing, which diminishes the availability of oviposition sites.…”
Section: Discussionmentioning
confidence: 99%
“…This intersexual difference was also recorded in other butterfly species, with females spending less time in flight, but covering larger distances and dispersing more often [ 33 , 34 , 35 , 36 ]. Such behaviour enables females to spread their eggs over a larger area, thus reducing potential intraspecific competition among their offspring [ 37 ]. On the other hand, male behaviour enables them to efficiently locate receptive females around their hatching place.…”
Section: Discussionmentioning
confidence: 99%